Ultrasound assessment of postplacental copper intrauterine device position 6 months after placement during cesarean delivery - Elizabeth P. Gurney; Arden McAllister; Britt Lang; Courtney A. Schreiber; Sarita Sonalkar (Elsevier, 2020)
Objective: The objective was to describe the sonographic position of copper intrauterine devices (IUDs) 6 months after insertion during cesarean delivery. Study design: This prospective, observational study followed participants who received a copper IUD during cesarean delivery. We performed pelvic examination at 6 weeks and 6 months and sonography at 6 months to determine IUD position. Patients had additional examinations as needed to address complications. Results: Sixty-nine participants provided outcomes through 6 months: 41 (59%) had correctly positioned IUDs, 21 (30%) had malpositioned intrauterine IUDs, 5 experienced expulsion (3 partial, 2 complete), and 2 had elective removal; 52 (75%) had missing strings. Missing strings at 6 weeks predicted an incorrect IUD position in 22 of 52 participants (positive predictive value 42%), and visible or palpable strings predicted a correct IUD position in 7 of 12 participants (negative predictive value 58%). Conclusion: Although 59% of copper IUDs placed during cesarean were correctly positioned at 6 months, nearly one third were malpositioned. Implications: Ultrasound may be indicated for patients receiving a copper IUD during cesarean delivery as checking IUD strings alone does not assure correct placement. Providers offering postpartum IUDs should ensure that appropriate processes for the evaluation and management of devices with missing strings or abnormal position are available to all patients regardless of insurance status.